A case report of subacute thyroiditis after inactivated SARS-CoV-2 vaccine - Umesha Nuwanrasee Wijenayake; Gowri Malka Ratnayake; Dilini Abeyratne; Uditha Sirimewan Bulugahapitiya (SAGE Open Medical Case Reports, 2022)
Subacute thyroiditis is an inflammatory thyroid disorder. It is often triggered following viral infections. Amid the current COVID-19 pandemic, several cases of subacute thyroiditis were reported worldwide related to SARS-CoV-2 infection and vaccines. We report a rare case of subacute thyroiditis possibly related to immunization with inactivated SARS-CoV-2 vaccine Sinopharm BIBP. A 29-year-old previously healthy Sri Lankan woman presented with anterior neck pain, low-grade fever and fatigue appearing 7 days after immunization with the second dose of inactivated SARS-CoV-2 vaccine Sinopharm BIBP. She apparently reported similar symptoms which subsided spontaneously within a few days, following immunization with first dose of vaccine. On examination, she had tenderness over the anterior neck. She was afebrile, not tachycardic and clinically euthyroid. Her inflammatory markers were elevated. An ultrasound scan of the neck demonstrated two low echogenic micronodules of 6 x 3 mm 2 and 5 x 3 mm 2 and low background thyroid vascularity. Technetium 99 m pertechnetate (Tc – 99 m) thyroidal uptake scan shows reduced thyroidal uptake suggestive of subacute thyroiditis. Thyroid function tests were normal at the time of the assessment. The patient was treated symptomatically with non-steroidal anti-inflammatory drugs. Her neck pain and tenderness resolved gradually. Serial measurements of thyroid functions during follow-up were within normal limits. Inflammatory markers normalized over the course of follow-up. Subacute thyroiditis following COVID-19 vaccination is a rare occurrence. However, due to its mild clinical course, it could very well be underreported. It is a mild and self-limiting illness with transient thyroid dysfunction; thus, it should be emphasized that the benefits of COVID-19 vaccination outweigh any rare and mild side effects reported.